The effect of five different sourdough on the formation of glyoxal and methylglyoxal in bread and influence of in vitro digestion - Ozgolet, Muhammed; Yaman, Mustafa; Durak, Muhammed Zeki; Karasu, Salih (ELSEVIER SCI LTD, 2022)
The aim of this study was to investigate sourdough impact on the in vitro bioaccessibility of Glyoxal (GO) and methylglyoxal (MGO). Five sourdough bread and one white bread (control bread) were prepared to observe sourdough influence on GO and MGO levels before and after in vitro digestion. GO and MGO levels increased in all breads after in vitro digestion. The highest increase in GO and MGO levels was realized in the control bread with bioaccessibility indexes (BIGO and BIMGO) of 8.67 and 4.14, respectively, whereas BIGO and BIMGO in sourdough breads were found in the range of 1.65 to 2.65 and 1.73 to 2.97, respectively. The extent of Maillard reaction (MR) in control bread was confirmed by FAST method. The lower increase in GO and MGO compounds after in vitro digestion thanks to sourdough addition may reduce bread's contribution of AGEs accumulation in the body.
Keywords: Dicarbonyls; Bioaccessibility; Sourdough; Maillard reaction; FAST Index; ALPHA-DICARBONYL COMPOUNDS; LACTIC-ACID BACTERIA; GLYCATION; FOODS; PRODUCTS; QUALITY; Chemistry; Food Science & Technology; Nutrition & Dietetics